1976
DOI: 10.1111/j.1432-1033.1976.tb10636.x
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Some Kinetic Properties of Soluble and Bound Lactate Dehydrogenase Isoenzymes at Different Temperatures

Abstract: A comparison was made of some kinetic properties of three chicken lactate dehydrogenase isoenzymes (1, 3 and 5) at 4, 16, 23 and 40°C. Assays were performed with an enzyme concentration of 0.01 pM at pH 6.0. Under the conditions of assay, lactate dehydrogenase 3 and 5 bound to the particulate fraction of homogenized skeletal muscle and were evaluated in the soluble and particulate state.Binding of isoenzymes 3 and 5 to the cellular particulate fraction decreased V. This decrease was much greater for lactate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…This phenomenon was also observed with other enzymes upon their association with membranes and was attributed to a reduced accessibility of exogenous radioactive substrate to the enzyme and/or to a "dilution" effect on the exogenous radioactive substrate; i.e. the presence of endogenous membrane phospholipids lowered the effective specific activity of the radioactive substrate (57)(58)(59). The normal Ca 2ϩ concentration in endothelial cells is approximately 70 nM (60,61), and in the current study lyso-PC was found to cause a 3-fold increase in the intracellular Ca 2ϩ level.…”
Section: Lyso-pc-induced Arachidonate Release In Endothelial Cellsmentioning
confidence: 68%
“…This phenomenon was also observed with other enzymes upon their association with membranes and was attributed to a reduced accessibility of exogenous radioactive substrate to the enzyme and/or to a "dilution" effect on the exogenous radioactive substrate; i.e. the presence of endogenous membrane phospholipids lowered the effective specific activity of the radioactive substrate (57)(58)(59). The normal Ca 2ϩ concentration in endothelial cells is approximately 70 nM (60,61), and in the current study lyso-PC was found to cause a 3-fold increase in the intracellular Ca 2ϩ level.…”
Section: Lyso-pc-induced Arachidonate Release In Endothelial Cellsmentioning
confidence: 68%
“…LDH activity was measured according to the modified method of Bergmeyer as previously published . The LDH isoenzymes in the total extracts of neurons and glial cells were separated according to the method of polyacrylamide disc electrophoresis of Nitisewojo and Hultin (1976). The densitometric recordings were performed on a Vernon microdensitometer.…”
Section: Methodsmentioning
confidence: 99%
“…However, the free energy of a biochemical reaction determines its direction, not the enzyme catalyzing it (Lehninger et al, 1993), so the dominant presence of LDH-1 in neurons does not influence the direction of the LDH reaction. Also, the lower V max of LDH-1 can offset the effects of its lower K m when the enzyme activity of LDH-1 is compared with that of LDH-5 (Nitisewojo and Hultin, 1976). Of greater importance is that LDH-1 is more sensitive to pyruvate product inhibition (K i ‫ס‬ 0.18 mM for LDH-1 and 0.28 mM for LDH-5) (Stambaugh and Post, 1966).…”
Section: The Ldh Isoform Distributionmentioning
confidence: 99%